Analysis of Strategies to Increase Waste Retribution Revenue in Central Maluku Regency - Ahmadi Seram; Maryam Sangadji; Maria K. Tupamahu (PT Mattawang Mediatama Solution, 2024)
Waste retribution is one of the sources of Regional Original Revenue (PAD), so its management needs to be maximized. However, there are still various obstacles faced by the Central Maluku Regional Government in increasing the contribution of restrinusi to PAD. The purpose of this study was to determine various internal and external factors that affect the receipt of waste retribution. The analysis method used is SWOT analysis which aims to determine strategies that can be formulated by Regional Governments. The results showed that the receipt of retribution was still low, so the strategy that must be rumplified by the government is an aggressive strategy